Language acquisition and academic writing theory and practice of effective writing instruction - Williams, James D. (James Dale) 1949- (New York Routledge, Taylor & Francis Group, 2023)
"An important contribution to the scholarship on student writing and composition theory, this book presents a new approach to writing instruction based in linguistic research and theory. In this book, leading scholar James D. Williams explores the historical failures of composition studies and the need for effective writing instruction to be grounded in the immersive principles of language acquisition. Starting with an inditement of the historical failures of composition studies to teach students how to become competent writers, the book moves beyond the current flawed theories and practices to introduce a new way forward to improving students' writing skills. Accessible and jargon-free, Williams skillfully explains how students must be immersed in target dialects and registers, with access to a range of authentic texts, to become effective writers of academic discourse. Chapters include authentic writing samples from the disciplines, including life and applied sciences, social sciences, and humanities. Essential for pre-service and practicing teachers of writing as well as scholars in composition and literacy studies, the book demonstrates how language acquisition is a valid foundation and provides a roadmap to improving students' writing proficiency"--
Theory and practice in composition studies -- Language acquisition and academic writing -- Analysis of academic writing -- Academic writing for success : implementing a language acquisition model.
Includes bibliographical references and index.
Keywords: English language -- Acquisition; Academic writing -- Study and teaching -- United States; Report writing -- Study and teaching -- United States; English language -- Composition and exercises -- Study and teaching -- United States; English language -- Rhetoric -- Study and teaching -- United States